Some Simulation Properties of the Major Euro Area Economies in Multimod - Laxton, Douglas; Hunt, Benjamin (Washington, D.C. : International Monetary Fund, 2003)
This paper was prepared as part of a euro area macroeconomic model comparisons project. Four standard macroeconomic experiments are considered to illustrate the differences in dynamic adjustment properties of two versions of MULTIMOD, the IMF's multicountry macroeconomic model. One version of MULTIMOD that is examined contains separate country blocks for the three major economies in the euro area, Germany, France, and Italy. The second, more recent version, contains a single block describing the behavior of the whole euro area.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet